2013
DOI: 10.1590/s0103-05822013000100009
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho funcional de crianças com paralisia cerebral de níveis socioeconômicos alto e baixo

Abstract: Objective: To investigate the influence of socioeconomic status on the functional performance of children with cerebral palsy.Methods: Cross-sectional quantitative study of 49 children diagnosed with cerebral palsy from a convenience sample. Children of both genders aged three to seven and a half years were studied. They were classified according to the level of severity of cerebral palsy based on the Gross Motor Function Classification System. Participants were organized in two groups considering their high o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
1
1
1
5
Order By: Relevance
“…Some studies were significantly related to the low economic class with motor difficulties (Grantham-Mcgregor et al, 2007;Assis-Madeira & Blascovi-Assis, 2013). The data from this study confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 83%
“…Some studies were significantly related to the low economic class with motor difficulties (Grantham-Mcgregor et al, 2007;Assis-Madeira & Blascovi-Assis, 2013). The data from this study confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of individuals in group 5 was 35.6%, and in group 4, 34.6%. 15 However, these data differed from those found in the present study, which showed a higher proportion of individuals in group 5 (75% in group 5 versus 25% in group 4), suggesting that the pattern of patients seen at the HC-UFU Outpatient Clinic for Special Patients was of more committed, more serious individuals, and that, in most cases, require specialized interdisciplinary follow-up due to the need to use an alternative feeding route.…”
Section: Discussioncontrasting
confidence: 99%
“…27 The results showed that using PEDI it was possible to investigate the relationship between family Socioeconomic Status (SES) and performance of children with CP, finding that children with low SES had less independence and more impaired functional skills. 28 Adopting PEDI, an investigation revealed the effect of follow-up with a speech therapist and physiotherapist and only with the physiotherapist of children with CP. It was found that there was no significant improvement in either area when comparing follow-up with one treatment and both.…”
Section: Resultsmentioning
confidence: 99%